DIGITALIZATION OF EDUCATION AT THE PRESENT STAGE OF DEVELOPMENT (World Bulletin of Management and Law, 2023)
Report talks about the informatization of education, a new stage in the development of society, "digitalization", the construction-(structure) of digital education, the digital generation and the digitalization of education at the present stage of the development of the information society.